Supply and demand dynamics and operational characteristics of the private sector dental care provision in Sri Lanka. - De Silva, M.D.K (My University, 2007)
The study consisted of four parts. First two parts of the study, surveyed the overall supply and demand dynamics. The third part surveyed the private dentistry in the district of Colombo, while the fourth surveyed the dental care product vendors. The methodology and the study design was such it enabled the research findings to be generalized to the entire country. A postal questionnaire, a self administered questionnaire, two interviewer administered questionnaires and two check lists were the study instruments used in this research. The results of the study showed that there were about 1000 private dental practitioners in Sri Lanka; there were more part-time practitioners than full time practitioners. The male dentists dominated the private dental care market both in number and in earnings. One tenth of the country's dentists were married to dentists. Inter as well as intra district inequality in service provision was a key feature in the private dental care delivery. The private dentistry showed varying degrees of market concentration depending on the locality and whether it was a full time practice or part time practice. A simple minority of dentists earned the majority of the income demonstrating a classic champagne glass pattern of income distribution. Only around 10 percent of the population used private dental care and the total value of the private dental care market was Rs 1.1 billion in 2006. The relatively small private dental care market in Sri Lanka is unorganized, unregulated, competitive and individualistic. The growth in supply has been relatively high compared to the growth in demand. Given the overall economic situation of the country, Sri Lanka may be facing an impending oversupply of dentists. The impending dental manpower oversupply may worsen if the demand continues to lag behind the increase in supply. The imbalance in dental manpower can lead to undesirable consequences at the professional, economic, health and social levels. The lowering of prestige and professional status of the dentist will be unavoidable. Facing an impending oversupply of dentists. The impending dental manpower oversupply may worsen if the demand continues to lag behind the increase in supply. The imbalance in dental manpower can lead to undesirable consequences at the professional , economic , health and social levels. The lowering of prestige and professional status of the dentist will be unavoidable. Establishment of a national planning and monitoring committee for oral health and entrust the task of strategic planning for oral health care. Further epidemiological studies must be carried out, to monitor provincial and national dental manpower levels based on population growth and demand for services. Reduction in the enrolment to the country's solitary Dental School should be considered as an urgent necessity. Steps should be taken to reduce the barriers to private dental care utilization